2019
DOI: 10.1136/bcr-2018-227757
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic carotid-cavernous fistula with bilateral proptosis simulating cavernous sinus thrombosis

Abstract: A 48-year-old woman presented with bilateral non-pulsatile proptosis and ophthalmoplegia after 3 days following blunt orbital trauma. It was associated with fever, malaise and loss of vision in right eye. She was provisionally diagnosed with cavernous sinus thrombosis and was treated with intravenous antibiotics with no improvement. A subtle bruit was present on examination, and digital subtraction angiography revealed a right direct (type A) carotid-cavernous fistula (CCF). The patient underwent right coil em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Nevertheless, as this study shows, diagnosing CCFs on CTA can be made difficult by normal anatomic variants, suboptimal timing of the contrast bolus, and asymmetry of structures that are often implicated as imaging evidence of CCFs. Furthermore, patients may present with a wide range of symptoms, which can also confound the diagnosis; nerve palsies, headaches associated with conjunctivitis, painful ophthalmoplegia, symptoms in the contralateral eye, and other non-specific symptoms have all been linked to CCFs (19)(20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, as this study shows, diagnosing CCFs on CTA can be made difficult by normal anatomic variants, suboptimal timing of the contrast bolus, and asymmetry of structures that are often implicated as imaging evidence of CCFs. Furthermore, patients may present with a wide range of symptoms, which can also confound the diagnosis; nerve palsies, headaches associated with conjunctivitis, painful ophthalmoplegia, symptoms in the contralateral eye, and other non-specific symptoms have all been linked to CCFs (19)(20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…CVST and CCF are rare complications of penetrating head trauma [ 3 , 4 ]. The diagnoses of CVST and CCF are difficult even with advanced neuroimaging because the signs and symptoms can be varied and non-specific.…”
Section: Discussionmentioning
confidence: 99%
“…A carotid cavernous fistula (CCF) is an abnormal connection between the cavernous sinus and the carotid arterial system. CCF is a very rare complication of head trauma, especially basal skull fracture [ 3 , 4 ]. We report a unique case of a penetrating brain injury by a needlefish causing orbital cellulitis, retro-orbital abscess, CVST and CCF.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature review, we found cavernous sinus embolism is almost invariably septic and is usually associated with a primary infective source in the face, throat, mouth, ear, mastoid, or in the sphenoidal, ethmoidal, or maxillary sinuses ( 4 7 ). Aseptic cavernous sinus embolism is a rare occurrence and has been described to be associated with head injury, surgical procedures of the fifth nerve, and carcinomatous invasion of the base of the skull ( 8 10 ). To our knowledge, venous tumor thrombus progressed cranially to the suprasellar region with painful ophthalmoplegia as the first manifestation of aseptic cavernous sinus embolism has not been previously reported.…”
Section: Discussionmentioning
confidence: 99%